SERS mapping in langmuir-blodgett films and single-molecule detection - Aoki, Pedro H.B. [UNESP]; Carreon, Eduardo G.E.; Volpati, Diogo [UNESP]; Shimabukuro, Milton H. [UNESP]; Constantino, Carlos J.L. [UNESP]; Aroca, Ricardo F.; Oliveira Jr., Osvaldo N.; Paulovich, Fernando V. (SAGE Publications, 2013)
Plasmon-enhanced spectroscopic techniques have expanded single-molecule detection (SMD) and are revolutionizing areas such as bio-imaging and single-cell manipulation. Surface-enhanced (resonance) Raman scattering (SERS or SERRS) combines high sensitivity with molecularfingerprint information at the single-molecule level. Spectra originating from single-molecule SERS experiments are rare events, which occur only if a single molecule is located in a hot-spot zone. In this spot, the molecule is selectively exposed to a significant enhancement associated with a high, local electromagnetic field in the plasmonic substrate. Here, we report an SMD study with an electrostatic approach in which a Langmuir film of a phospholipid with anionic polar head groups (PO 4 -) was doped with cationic methylene blue (MB), creating a homogeneous, two-dimensional distribution of dyes in the monolayer. The number of dyes in the probed area of the Langmuir-Blodgett (LB) film coating the Ag nanostructures established a regime in which single-molecule events were observed, with the identification based on direct matching of the observed spectrum at each point of the mapping with a reference spectrum for the MB molecule. In addition, advanced fitting techniques were tested with the data obtained from micro-Raman mapping, thus achieving real-time processing to extract the MB single-molecule spectra. © 2013 Society for Applied Spectroscopy.
Keywords: SERS; Single-molecule detection (SMD); Visual data exploration; Micro-Raman mapping; Realtime processing; Single molecule level; Single-molecule detection; Spectroscopic technique; Two dimensional distribution; Aromatic compounds; Electromagnetic fields; Mapping; Molecular biology; Phospholipids; Plasmons; Silver; Substrates; Molecules